GREEN ECONOMY AS A FACTOR INFLUENCING THE ENSUREMENT OF SUSTAINABLE DEVELOPMENT OF THE LABOR MARKET AND JOBS IN UZBEKISTAN (International journal of artificial intelligence, 2026)
This article explores the impact of the green economy on the labor market and the modernization of workplaces in Uzbekistan. It highlights the role of state support and educational programs, alongside an analysis of employment growth trends within the renewable energy sector. The study examines the development of green energy as a pivotal factor for economic growth and enhancing the country's global competitiveness. Furthermore, the paper identifies risks associated with climate change and automation, while proposing strategic measures to ensure a just transition to a sustainable economy.